J Plant Pathol Microbiol 2020
DOI: 10.35248/2157-7471.20.11.489
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism Potential of Trichoderma viride against Erysiphe necator in the Culture of Grapevine under Field Conditions

Abstract: The vine is a crop affected by various pests and diseases. Being the oidium produced by Erysiphe necator one of the most important. Generally the farmer, due to lack of knowledge makes an inappropriate use of fungicides, which is harmful, since the intensive use (and sometimes excessive) of chemical products has had negative effects on the environment and the quality of life of human populations. That is why the present investigation set out to develop a clean technology with the use of antagonistic fungi Tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Prophylactic applications of a commercial product based on Trichoderma viride strain CCBLA103, every week from the inflorescence stage to the berry ripening stage, showed that exclusive applications of the biocontrol agent on V. vinifera cultivar Italia showed more than 80% efficacy in disease management (Yparraguirre et al, 2020).…”
Section: Fungimentioning
confidence: 99%
“…Prophylactic applications of a commercial product based on Trichoderma viride strain CCBLA103, every week from the inflorescence stage to the berry ripening stage, showed that exclusive applications of the biocontrol agent on V. vinifera cultivar Italia showed more than 80% efficacy in disease management (Yparraguirre et al, 2020).…”
Section: Fungimentioning
confidence: 99%